The Relationship of Knowledge and Mother's Attitude to Stunting Incidence in Kutelintang Village, Gayo Lues District Year 2022 - Yusridawati (Science Midwifery, 2022)
Stunting is a big problem because it can result in high mortality rates, failure to thrive, cause cognitive and motoric problems in children, risk obesity and less than optimal learning achievement. The incidence of stunting in Nangroe Aceh Darussalam (NAD) in 2018 was 10 .69%. and this figure has increased in 2019 to 12.37% The highest prevalence of stunting is in Gayo Lues Regency at 17.94%.Research objectivesTo knowRelationship between knowledge and mother's attitude towards stunting in Kutelintang Village, Gayo Lues Regency in 2022. This type of research is descriptive correlation, cross sectional design. The population in this study were all mothers who had toddlers. in the village of Kutelintang there were 30 people. The sampling technique was total sampling. The data was taken by questionnaire and direct observation, and processed by the Chi Square test. The results showed that the majority had less knowledge of 12 people (40.0%), had a negative attitude towards stunting as many as 18 people (60.0%) and stunting occurred as many as 21 people (70.1%). 12 people (40%), the results of the Chi Square test, namely the results obtained p value = 0.002. This value is <0.05 so that Ha is accepted, which means there is a significant relationshipAmongKnowledge with Mother's Attitudes Against Stunting Incidents in Kutelintang Village, Gayo Lues Regency in 2022. The results of the study were obtainedthere isThe Relationship between Knowledge and Mother's Attitude towards Stunting Incidents in Kutelintang Village, Gayo Lues Regency in 2022, it is recommended to Health Officers to recommend mothers to take Height and Weight Measurements and regulate eating patterns.